PREVALENCE AND POTENTIAL RISK FACTORS ASSOCIATED WITH KETOSIS IN DAIRY FARMS IN EGYPT - Mohamed Marzok; Sabry El-khodery; Hussein Babiker; Ghada G. Afifi; Ahmed M. Abdelaal; Katharigatta N. Venugopala; Mahmoud Kandeel; Magdy Elgioushy (Slovenian Veterinary Research, 2024)
Ketosis is an energy-related metabolic disease that primarily occurs during the early lactation period in dairy cattle. Ketosis adversely affects production, animal health, and reproduction. The present study determines the prevalence and risk factors associated with ketosis in dairy cattle during early lactation in Egypt. A total of 1179 dairy cows from 37 dairy farms were screened for ketosis using a semi-quantitative cow-side milk strip test. A questionnaire was constructed to include the hypothesized risk factors. Risk factors were assessed on both the cow and herd levels using logistic regression model. The findings showed that the prevalence of ketosis was 6.35% (75/1179 cases). On the cow level, the final logistic regression model revealed a significant association between ketosis and parity ≥4 (P= 0.040, OR: 1.74, CI 95%: 1.025–2.95), cows with a dry period length ≥ 65 days (P =0.02, OR: 1.88, CI 95%: 1.1–3.18), calving season (P=0.037, OR: 1.73, CI 95%: 1.03–2.89), BCS>3.5 (P= 0.010, OR: 2.03, CI 95%: 1.19–3.47), milk yield ≥25L/day (P= 0.033, OR 2.04, CI 95%: 1.06-3.92), dystocia (P< 0.001; OR: 3.18, CI 95%: 1.75–5.77), retained placenta (P= 0.006, OR: 2.85, CI 95%: 1.35-6.032), and displaced abomasum (P< 0.001, OR: 26.28; CI 95%: 7.20–95.90). On the herd level, there was an association between ketosis and insufficient prepartum feeding of a total mixed ration (P= 0. 021, OR: 6.29, CI 95%: 1.325–29.86), and in herds deficient-lactation supplementation propylene glycol (P= 0.047, OR: 4.86, CI 95%: 1.020–23.19). In conclusion, ketosis is an existing problem in dairy farms in Egypt; therefore, identification of risk factors may provide a useful approach for the prevention and control such metabolic problems.